Factors Affecting the Dividend Policy of Companies: A Meta-analysis Approach - Yalda Hassani; Bagher Asgarnezhad Nouri; Ghasem zarei; Allahyar Beigi Firoozi (Journal of Asset Management and Financing)
A dividend is considered to represent the company's financial commitment to shareholders to pay a part of their investment returns, which requires the use of appropriate policies and the identification of factors affecting it in order to manage future cash flows for the company. Various studies have been conducted that have introduced various factors affecting the dividend policy, such as capital structure, agency cost, accounting reporting, and the effective tax rate, but the results have been contradictory and scattered. For this purpose, conducting comprehensive research with a meta-analysis approach regarding determining the importance of each of the effective factors on the dividend policy in order to achieve a general summary and resolve the contradictions and dispersion of the results seems necessary. To review the previous research, first, the desired variables were determined, and then the necessary information was collected for 196 studies until 2021. Based on systematic elimination sampling, the number of remaining studies that had the necessary characteristics to enter the meta-analysis process was equal to 123 studies. We coded and entered the extracted data into CMA2 statistical software. The effect size was calculated, and the homogeneity and heterogeneity of the effect size were evaluated. The results of this study showed that the factors of corporate governance mechanism and agency cost did not affect the company's dividend policy. However, the positive effect of free cash flow factors, profitability ratios, quality of financial reporting, effective tax rate, capital structure, institutional investors, information asymmetry, ability of managers, and concentration of ownership in dividend policy was confirmed.